Electrochemical nickel-induced fluoroalkylation: synthetic, structural and mechanistic study - Mikhaylov, Dmitry; Gryaznova, Tatyana; Dudkina, Yulia; Khrizanphorov, Mikhail; Latypov, Shamil; Kataeva, Olga; Vicic, David A.; Sinyashin, Oleg G.; Budnikova, Yulia (Dalton transactions : an international journal of inorganic chemistry, 2012)
Electrocatalytic generation of nickel catalysts in low oxidation states by reduction of nickel complexes with various ligands (2,2'-bipyridine, 2,2':6',2''-terpyridine, (S,S)-2,6-bis(4-phenyl-2-oxazolin-2-yl)-pyridine) in the presence of olefinic substrates and fluoroalkyl halides leads to new organic products derived from addition-dimerization processes. Due to the presence of two stereocenters in the dimerization products two diastereomers were characterized by a variety of analytical techniques including multi-dimensional NMR methods and X-ray single crystal diffraction. The formation of dimers was prevented by the inclusion of the hydrogen atom donor tributyltin hydride. The cyclic voltammetry study of selected nickel complexes along with fluoroalkyl halides demonstrated that Ni(I)L is the active form of the catalyst.